Females' Peer Influence and Support for Adolescent Males Receiving Voluntary Medical Male Circumcision Services. (3rd April 2018) - Kaufman, Michelle R; Dam, Kim H; Sharma, Kriti; Van Lith, Lynn M; Hatzold, Karin; Marcell, Arik V; Mavhu, Webster; Kahabuka, Catherine; Mahlasela, Lusanda; Patel, Eshan U; Njeuhmeli, Emmanuel; Seifert Ahanda, Kim; et al.
Abstract: Background: While female involvement in voluntary medical male circumcision (VMMC) has been studied among adults, little is known about the influence of adolescent females on their male counterparts. This study explored adolescent females' involvement in VMMC decision making and the postoperative wound healing process in South Africa, Tanzania, and Zimbabwe. Methods: Across 3 countries, 12 focus group discussions were conducted with a total of 90 adolescent females (aged 16–19 years). Individual in-depth interviews were conducted 6–10 weeks post-VMMC with 92 adolescent males (aged 10–19 years). Transcribed and translated qualitative data were coded into categories and subcategories by 2 independent coders. Results: Adolescent female participants reported being supportive of male peers' decisions to seek VMMC, with the caveat that some thought VMMC gives males a chance to be promiscuous. Regardless, females from all countries expressed preference for circumcised over uncircumcised sexual partners. Adolescent females believed VMMC to be beneficial for the sexual health of both partners, viewed males with a circumcised penis as more attractive than uncircumcised males, used their romantic relationships with males or the potential for sex as leveraging points to convince males to become circumcised, and demonstrated supportive attitudes in the wound-healing period. Interviews with males confirmed that encouragement from females was a motivating factor in seeking VMMC. Conclusions: Adolescent female participants played a role in convincing young males to seek VMMC and remained supportive of the decision postprocedure. Programs aiming to increase uptake of VMMC and other health-related initiatives for adolescent males should consider the perspective and influence of adolescent females.